Conducting Successful Focus Groups and Analysis: Experience from a Pilot Study on Family Planning and Sexual Behaviour in the Era of HIV/AIDS and STDs - Neema, Stella (African Journal of Reproductive Health, 1998)
The pilot was a qualitative study using four focus group discussions (FGD's). It was undertaken district among sexually active men and female contraceptive users and non-users. The pilot focus discussions were conducted to test FGD guidelines developed to collect contextual and attitudinal family planning and issues related to sexual health in the community. A further aim of the pilot to develop a coding schedule for the analysis of focus groups discussions and to formulate tips ducting and analyzing successful FGDs and their analysis to ass
Keywords: Focus group; Qualitative methods; Family planning; sexual behaviour